The study of optical gain for terahertz quantum cascade laser using density matrix method - Mohd. Akil, M. A. (Penerbit UTM Press, 2016)
Terahertz (THz) quantum cascade lasers (QCL) are currently increasing in popularity. It is expected to become the main source of emerging terahertz radiation technology and applications. However to produce the device within the application specification is costly and time consuming. This is because the manufacturing process of the superlattice growth and the device processing and testing are long and expensive processes. Thus a prediction tool is needed to overcome the problems in designing and producing THz QCL within the needed optical expectation. The density matrix method is used to calculate the performance of this device electronically and optically. The result obtained was compared to the experimental result conducted by previous researchers. The calculation result showed that the gain is 20 cm−1 when the population inversion occurs at threshold current density of 400 A cm-2. Meanwhile a negative gain or loss occurs below 350 A cm-2. As a conclusion, it is demonstrated that this method has a capability to explain the transport phenomena as well as to predict the performance of the THz QCL device design.